Pemanfaatan Sistem QRIS Untuk Meningkatkan Transaksi UMKM di Warung King Dimsum Desa Karangmekar Kec. Karangsembung, Kab. Cirebon - Muhammad Fajar Juliyanto; Irvansyah Irvansyah; Muhammad Yusuf Faisal; Dhani Ramadhon; Gabriella Elshadday; Nur Ratnasari; Stylla Destrian Hartiono; Aliyah Nurhanipah Rusmawan; Almatina Denaya Putri; Rifka Faradila Putri; Ade Elza Surachman (Pusat Riset dan Inovasi Nasional, 2025)
Digital transformation through cashless payment systems has become a crucial need for MSMEs to improve business efficiency and competitiveness. This community service program aims to implement and effectively use the Quick Response Code Indonesian Standard (QRIS) at Warung K1ng Dimsum in Karangmekar Village, Karangsembung District, Cirebon Regency. The methods used were interviews with business owners and questionnaires distributed to 56 customer respondents. The results of the activity showed that the implementation of QRIS was very well received and had a positive impact in the form of a 17% increase in the number of transactions within one week of implementation. In addition, QRIS helps in more orderly financial records, speeds up the transaction process, and increases customer convenience. These findings indicate that appropriate education and mentoring can encourage MSMEs to digitally transform and strengthen their position in the modern economic ecosystem. The successful implementation of QRIS at Warung K1ng Dimsum also shows that implementing digital technology does not always require large investments, but requires commitment and readiness from business owners to change. In addition to simplifying transactions, this digital payment system opens up opportunities for MSMEs to connect with other formal financial services, such as access to digital capital and integration with bold sales platforms. Therefore, collaboration between the government, financial institutions, and educational institutions is crucial in providing continuing education and technical support so that the digital transformation of MSMEs can proceed equitably and sustainably. The implementation of QRIS is also the first step in creating a more transparent and accountable business ecosystem for MSMEs. Therefore, digitalization through QRIS not only impacts operational aspects but also opens up opportunities for increasing long-term competitiveness.